An inconspicuous, conspicuous new species of Asian pipesnake, genus Cylindrophis (Reptilia: Squamata: Cylindrophiidae), from the south coast of Jawa Tengah, Java, Indonesia, and an overview of the tangled taxonomic history of C. ruffus (Laurenti, 1768) - Kieckbusch, Max; Mecke, Sven; Hartmann, Lukas; Ehrmantraut, Lisa; O’shea, Mark; Kaiser, Hinrich (Zootaxa, 2016)
We describe a new species of Cylindrophis currently known only from Grabag, Purworejo Regency, Jawa Tengah Pro-vince (Central Java), Java, Indonesia. Cylindrophis subocularis sp. nov. can be distinguished from all congeners by the presence of a single, eponymous subocular scale between the 3rd and 4th or 4th and 5th supralabial, preventing contact between the 4th or 5th supralabial and the orbit, and by having the prefrontal in narrow contact with or separated from the orbit. We preface our description with a detailed account of the tangled taxonomic history of the similar and putatively wide-ranging species C. ruffus, which leads us to (1) remove the name Scytale scheuchzeri from the synonymy of C. ruffus, (2) list the taxon C. rufa var. javanica as species inquirenda, and (3) synonymize C. mirzae with C. ruffus. We provide additional evidence to confirm that the type locality of C. ruffus is Java. Cylindrophis subocularis sp. nov. is the second species of Asian pipesnake from Java.